Oral health knowledge among healthcare personnel and their challenges in dealing with patients’ oral health problems - Dzulqarnain Ahmad Iskandar Shah,; Nursabrina Roslan,; Khairun ‘Izzah Zamansari,; Tuan Nur Athirah Tuan Mohd Rahimi,; Mohd Fairuz Ali,; Haslina Rani,; Tuti Ningseh Mohd-Dom,; Shahida Mohd Said, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The role of non-dental healthcare personnel (HCP) in promoting oral health is well-accepted yet efforts in training them to be competent in delivering this role are inadequate. This study is aimed to assess the HCP’ oral health and care knowledge, and explore possible challenges faced by HCP in managing oral health problems among their patients in a public primary healthcare clinic. A focus group discussion was carried out involving ten HCP directly involved with patients from different units within the health clinics. Questions were asked in two parts: (i) knowledge on oral health and its link to general health, and (ii) issues and challenges faced by HCP with patients having oral health problems in their daily routine. The session was recorded on a digital audio tape, responses were then transcribed, scripts were grouped and lastly analysed qualitatively. Majority of the participants appeared to have a good knowledge on general and oral health but only very few were aware on the relationship between oral health problems with systemic conditions. Among the main challenges faced by HCP when dealing with patients with oral health problems were limited knowledge on oral health problems including management of medically compromised patient requiring dental treatment and difficulty in changing the mindset of patients regarding oral health issues especially on seeking dental treatment. In conclusion, most of the participants agreed on the need for additional relevant training to enable them to provide coordinated and comprehensive service to patients with oral health problems in the primary healthcare clinics.